Influence of the public gestión to develop the tourisa in the Buenaventura port (2015)
Is o ne of the tourist attractions that has Colombia. Its geographical positions is strategic to the business with the rest of the world. The state and the private company to invest in the port, they have a commitment to improve the quality of life in this región. Therefore they continue projecting inversion to make. Of this commercial corridor a place of opportunities and then, use the benefits offered by that community as: Exotic beaches, variety in food, own music those aspects summarize two cultures, friendly people and with idiosyncrasies, maritime wealth, mining, forestry, and a magnificent geographical position. Finally it is important to mention the current investment as public as private in the región.